Advances in aflatoxins monitoring of stored food - Da Rodrigueiro, Mariana Matulovic Silva [UNESP]; De Amorim, Cleber Alexandre [UNESP]; Oliveira, Kassandra Sussi Mustafé [UNESP]; De Morais, Flávio José Oliveira [UNESP]; Joshi, Priyanka; Blanco, Kate Cristina (AMG Transcend Association, 2022)
This review provides relevant advances in detecting fungal aflatoxins from agro-industrial products during their development, storage, and processing. For real-time monitoring of these toxins, methodologies were modified and adapted over time. The description of the current literature and the evolution of detection and quantification of aflatoxin in agro-products contaminated by fungi is carried out with the description, mainly of chromatographic, immunochemical, spectroscopic, and genomic methods. In addition to equipment, several methodologies were developed and adapted to improve the specificity of mycotoxin detection through faster analyzes focusing on food safety.
Keywords: Aflatoxin; Agricultural products; Detection; Food; Mycotoxins